Principles of design (Art is., 1996)
Shows how the seven elements of design are combined and used in developing the seven principles of design : rhythm, unity, contrast, emphasis, pattern, movement, and balanace. Each principle is explained with diagrams and reinforced with hands-on demonstrations.